2016
DOI: 10.1080/19420862.2016.1228505
|View full text |Cite
|
Sign up to set email alerts
|

Methylated α-tubulin antibodies recognize a new microtubule modification on mitotic microtubules

Abstract: Posttranslational modifications (PTMs) on microtubules differentiate these cytoskeletal elements for a variety of cellular functions. We recently identified SETD2 as a dual-function histone and microtubule methyltransferase, and methylation as a new microtubule PTM that occurs on lysine 40 of a-tubulin, which is trimethylated (a-TubK40me3) by SETD2. In the course of these studies, we generated polyclonal (a-TubK40me3 pAb) and monoclonal (a-TubK40me3 mAb) antibodies to a methylated a-tubulin peptide (GQMPSD-Kme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Cells were lysed by gentle pipetting several times and incubated on ice for 10 mins in a cell fractionation buffer (320 mM sucrose, 10mM Tris-HCl (pH8.0), 2mM magnesium acetate, 3 mM calcium chloride, 0.1 mM EDTA, 0.5% NP-40, fresh 1mM dithiothreitol, protease inhibitor cocktail, 1 mM PMSF, and 1 mM sodium orthovanadate). Cytoplasmic fractions were collected after centrifugation at 1,000 g for 5 min and were used for western blots using antibodies against α-TubK40me3 (18, 23) or α-tubulin (MA1-19162, Thermo Fisher Scientific, Waltham, MA). The nuclear proteins were extracted in cell lysis buffer (20 mM Tris-HCl (pH7.5), 150 mM NaCl, 1mM EDTA, 1 mM EGTA, 1% Triton X-100, and protease inhibitor cocktail) by sonication for 3 cycles of 30 secs on/off using Bioruptor 300 (Diagenode, Denville, NJ) and used for western blots using antibodies against SETD2 (HPA042451, Sigma-Aldrich, St. Louis, MO), H3K36me3 (61101, Active Motif, Carlsbad, CA) or histone H3 (ab1791, Abcam, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed by gentle pipetting several times and incubated on ice for 10 mins in a cell fractionation buffer (320 mM sucrose, 10mM Tris-HCl (pH8.0), 2mM magnesium acetate, 3 mM calcium chloride, 0.1 mM EDTA, 0.5% NP-40, fresh 1mM dithiothreitol, protease inhibitor cocktail, 1 mM PMSF, and 1 mM sodium orthovanadate). Cytoplasmic fractions were collected after centrifugation at 1,000 g for 5 min and were used for western blots using antibodies against α-TubK40me3 (18, 23) or α-tubulin (MA1-19162, Thermo Fisher Scientific, Waltham, MA). The nuclear proteins were extracted in cell lysis buffer (20 mM Tris-HCl (pH7.5), 150 mM NaCl, 1mM EDTA, 1 mM EGTA, 1% Triton X-100, and protease inhibitor cocktail) by sonication for 3 cycles of 30 secs on/off using Bioruptor 300 (Diagenode, Denville, NJ) and used for western blots using antibodies against SETD2 (HPA042451, Sigma-Aldrich, St. Louis, MO), H3K36me3 (61101, Active Motif, Carlsbad, CA) or histone H3 (ab1791, Abcam, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The recent guidelines of the National Heart, Lung, and Blood Institute to treat the complications of SCD did not adequately address this issue. 5,6 In addition, a recent Cochrane review of fluid replacement therapy for acute episodes of pain in people with SCD found no randomized controlled trials that have assessed the safety and efficacy of different routes, types, or quantities of fluid.…”
mentioning
confidence: 99%
“…Recently, methylation has been found on tubulins occurring in lysine and arginine amino acid residues [22,75,76,77,78,79,80] and it has not been characterized in detail.…”
Section: Resultsmentioning
confidence: 99%
“…All these features, including post-transcriptional and post-translation mechanisms, represent a hallmark of the tubulin multigene family and the polymer structural diversity [74,75,76].…”
Section: Resultsmentioning
confidence: 99%